Calls of five species of the Scinax ruber (Anura: Hylidae) clade from Brazil with comments on their taxonomy - Magrini, Leandro; de Carvalho-E-Silva, Sergio P.; Béda, Arlindo F.; Giaretta, Ariovaldo A. (Zootaxa, 2011)
As currently defined, tree frogs of the genus Scinax comprises the most species-rich genus within Hylinae. Although in the last decades there have been an increasing number of taxonomic studies on Scinax, populations of several species still deserve further studies to assess their taxonomic status. The purpose of this paper is to contribute to the taxonomy and zoogeography of some species of Scinax from Brazil assigned to the Scinax ruber clade through the description/redescription of their advertisement calls. The advertisement call of S. duartei from topotypic specimens and the call of S. acuminatus are described here for the first time. The call of S. duartei is in disagreement with descriptions from the literature what suggests that an unnamed species is hidden under this specific name. Redescriptions of the calls of S. crospedospilus, S. eurydice, and S. hayii are also provided and compared with previous studies. In order to better assess the taxonomic status of species with advertisement calls that present more than one emphasized frequency, as in some species of the Scinax ruber clade, we recommend special attention in the descriptions of the spectral components of these calls.